Correlation the Cytomegalovirus (CMV) IgM Antibodies and Viral DNA Presence with Rheumatoid Arthritis (RA) in Iraqi Patients - Fadhil, Hula Y. (Iraqi Journal of Science, 2019)
In the Iraqi population, a high incidence (82.7%) of rheumatoid arthritis (RA) has been reported among the suspected patient. Many investigators studied the microbial infectious present in Iraqi patients with RA; however, to the best of our knowledge, there is no previous study detected the CMV DNA and antibodies to RA disease. Hence, the current study aimed to investigate the presence of CMV DNA and antibodies in Iraqi RA patients. A total of 58 blood samples were collected from patients with clinical signs of rheumatoid arthritis, along with 32 samples of apparently healthy individuals as a control group. These samples were tested for rheumatoid factor (RF), CMV IgM antibodies and viral DNA during the acute and the chronic periods of the autoimmune disease. The results showed that 46.6% (27/58) and 13.8% (8/58) of rheumatoid arthritis patients had positive reactions for IgM-CMV and CMV DNA, respectively, as compared to healthy individual. The highest rate of the viral occurrence was recorded in the aged and female RA patients (24 and 21 cases, respectively). Moreover, the most significant increases in RA appearance and CMV reactivation cases were observed in patients with a mean age higher than 40 years old. This finding pointed out the prevalence of viral infections mostly in RA patients aged more than 40 years old, accompanied by increased RA cases. This study concludes that patients with positive CMV must be tested for rheumatoid factor, especially when the viral DNA is present. Moreover, we recommend measuring TNF-Î± and IFN-Î³ as the proinflammatory cytokines that play an important role to protect against viral infection and prevent their reactivation in all RA patients.